Transformasi Kompetensi SDM dan Komunikasi Layanan di Era Digital: Tinjauan Strategis Manajemen Sumber Daya Manusia (Lembaga Pengembangan Kinerja Dosen, 2026)
The rapid development of information technology in the Industrial Revolution 4.0 era demands a fundamental transformation in Human Resource Management (HRM) practices. The main challenge organizations face today is the skill gap between industrial digitalization demands and workforce readiness, especially in maintaining customer service interaction quality. This study aims to analyze comprehensive strategies to increase HR productivity through strengthening digital competence, adaptive business communication, and adopting HRM technology. This research uses the Systematic Literature Review (SLR) method by reviewing 20 reputable journal articles (International and National) published between 2021 and 2025. The results show that improving service performance cannot rely solely on technology adoption but requires the integration of